1987
DOI: 10.1161/01.str.18.4.808
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous internal jugular vein thrombosis and venous-stasis retinopathy.

Abstract: A case is presented in which the detection of venous-stasis retinopathy in one eye led to investigation of the carotid circulation. There were no neurologic symptoms of carotid insufficiency, and noninvasive tests failed to reveal significant carotid pathology. Digital subtraction angiography and carotid angiography demonstrated a carotid plaque of doubtful significance. At carotid endarterectomy, the venous-stasis retinopathy was found to be associated with venous thrombosis distant from the eye and in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Gutteridge et al [6] reported a case of spontaneous IJVT who had a history of previous probable internal jugular vein catheterization during an aortic aneurysm operation although not stated clearly. Kennedy et al [5] reported a case of spontaneous IJVT whose erythrocyte sedimentation rate was 80 mm/h and the fibrinogen level 400 mg/dl.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gutteridge et al [6] reported a case of spontaneous IJVT who had a history of previous probable internal jugular vein catheterization during an aortic aneurysm operation although not stated clearly. Kennedy et al [5] reported a case of spontaneous IJVT whose erythrocyte sedimentation rate was 80 mm/h and the fibrinogen level 400 mg/dl.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies in the literature related to IJVT of unknown origin [5,6]. Gutteridge et al [6] reported a case of spontaneous IJVT who had a history of previous probable internal jugular vein catheterization during an aortic aneurysm operation although not stated clearly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Other complications include distal propagation of thrombus resulting in intracerebral venous sinus thrombosis 2,18,21 and retinopathy resulting in vision loss. 13,21 The only reported case of trauma-related IJV thrombosis occurred in a young assault victim, in whom clinical assessment had revealed anterior neck haematoma and diffuse oedema of the face and scalp. 9 Investigative carotid angiography revealed the presence of bilateral IJV thromboses, subsequently treated successfully using anticoagulation over a 6-week period.…”
Section: Discussionmentioning
confidence: 99%
“…[2] However, it can complicate as septic embolism, pulmonary embolism, elevated intracranial pressure or intracranial venous thrombosis. [34] Sub-arachnoid hemorrhage (SAH) induces a prothrombotic state with moderate risk (10-40%) for developing DVT. [5] Presence of reduced intravascular volume can further increase this risk as occurs in SAH.…”
mentioning
confidence: 99%